JURIDICAL ANALYSIS OF THE APPLICATION FOR THE ORIGIN OF CHILDREN OUT OF WEDLOCK AGAINST THE CHILD PROTECTION LAW (CASE STUDY AT THE BATAM RELIGIOUS COURT) - Erniyanti; Cut Ria Mariana; Parameshwara (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Legal matters concerning the status of children born out of wedlock remain intricate and necessitate specialized treatment within the national legal framework, particularly with the safeguarding of children's civil rights. A legal measure to secure recognition for children born out of wedlock involves applying to the establishment of parentage in the Religious Court. This study seeks to examine the legal foundations and procedures for applications concerning the status of out-of-wedlock children presented to the Batam Religious Court. It aims to assess the implementation and legal ramifications of the court's rulings on the legal status of these children and their implications for the children's civil rights, while also formulating legal solutions to enhance protection for children born outside of wedlock. This study employs normative juridical and empirical juridical methodologies by analyzing laws and regulations, specifically Constitutional Court Decision No. 46/PUU-VIII/2010, alongside five rulings on child origin cases from the Batam Religious Court as primary data sources. The theoretical framework employed includes Justice Theory as the overarching theory, Legal System Theory as the intermediary theory, and Maslahah Mursalah Theory as the practical application theory. The research findings indicate that the Batam Religious Court typically dismisses applications about a child's lineage in the absence of acceptable marital evidence under Islamic law, despite the presence of biological evidence such as DNA test results. Consequently, the child fails to establish a civil relationship with their father and forfeits certain essential legal rights. Consequently, the alignment of Islamic law, national law, and population administration law is essential, along with the formulation of a national Standard Operating Procedure that prioritizes child protection and non-discrimination principles.